Cross-Sectoral Portfolio Optimization in Emerging Markets: Value at Risk Assessment of Indonesian Consumer and Financial Stocks - Ahmar, Ansari Saleh; Wahyuni, Wahyuni; Triutomo, Agung; Rahman, Abdul; Tabash, Mosab (Quantitative Economics and Management Studies, 2025)
This study examines the comparative risk profiles of single-asset investments versus portfolio strategies using two prominent Indonesian companies: PT. Mayora Indah and PT. Sinar Mas Multiartha. Employing a quantitative approach with Monte Carlo simulation and Value at Risk (VaR) methodology, the research analyzed daily stock returns over a one-year period (January-December 2023). Results reveal that despite similar historical volatility levels between the individual stocks (standard deviations of 2.65% and 2.88%), their correlation coefficient was notably low (0.13), creating significant diversification opportunities. Monte Carlo simulations generated 1,000 potential return scenarios for robust risk assessment, finding that at the 95% confidence level, maximum expected losses on a Rp 100 million investment were Rp 4.78 million for PT. Mayora Indah and Rp 4.58 million for PT. Sinar Mas Multiartha individually. However, a portfolio combining both stocks (60% PT. Mayora Indah, 40% PT. Sinar Mas Multiartha) reduced this potential loss to Rp 2.90 million—representing approximately 37% risk reduction compared to either single-asset investment. This substantial risk mitigation was consistent across all confidence levels (99%, 95%, and 90%). The portfolio also demonstrated improved return characteristics in simulation (0.39% expected return) compared to historical data (0.09%), while maintaining similar risk levels. These findings provide empirical support for the practical value of diversification strategies in the Indonesian equity market, highlighting how even limited diversification across two stocks from different economic sectors can yield substantial improvements in risk-adjusted investment outcomes.